Cytotoxic potential of the Red Sea sponge Amphimedon sp. supported by in silico modelling and dereplication analysis. Issue 24 (17th December 2021) - Shady, Nourhan Hisham; Abdelmohsen, Usama Ramadan; AboulMagd, Asmaa M.; Amin, Mohamed N.; Ahmed, Safwat; Fouad, Mostafa A.; Kamel, Mohamed Salah
Abstract: The chemical profile of the butanol fraction of the Red Sea sponge Amphimedon sp. was explored using liquid chromatography coupled with high-resolution mass spectrometry and identified compounds (1–11 ). Moreover, cytotoxic activities of the total extract and other fractions were examined against three cell lines HEPG2, MCF7 and CACO2, revealed the powerful effect of the total extract and the butanol fraction against the three cell lines. Further chromatographic separation of the active butanol fraction yielded the isolation of three known compounds (9–11 ). Molecular modelling was carried out with the active site of the SET protein. Docking study results revealed that amphiceramides A-B (7–8 ) and acetamidoglucosyl ceramide (6 ) showed the highest energy binding affinities and interaction in the binding site of SET protein. Additionally, ADME/Tox calculations were performed for the compounds to predict their pharmacokinetics profile. These results highlighted the valuable chemical entities of Amphim edon sp. as lead source for cytotoxic natural products. Graphical Abstract: UF0001